Investigating strategies to reduce pain in piglets undergoing surgical castration and tail docking - Lou, Maria Elizabeth (Kansas State University, 2024)
Within their first week of life, millions of piglets raised each year on commercial swine farms undergo routine husbandry procedures including tail docking and surgical castration. Extensive research has demonstrated that these procedures elicit behavioral and physiological responses associated with stress and pain in piglets. However, these procedures are commonly performed without the use of analgesia or anesthesia for pain relief. This constitutes a significant animal welfare concern as these procedures negatively affect the quality of life of piglets both in the short-and-long term. Therefore, research focused on assessing pain in piglets to determine effective pain mitigation strategies and processing tools that cause less pain are needed. Research on this topic proves challenging as pigs naturally mask signs of pain and weakness being a prey species. Additionally, animal-based indicators that are objective and can reliably detect pain in piglets over time are essential in gaining drug approval from the U.S. Food and Drug Administration for pain control in swine. As there are currently no drugs with FDA-approval for this purpose, veterinarians and producers are faced with a major obstacle in implementing piglet pain management protocols. The aim of this research is to improve the welfare of piglets on-farm. In this dissertation, study objectives were to evaluate analgesic strategies and the utility of CO₂ surgical laser in reducing pain in piglets after tail docking and surgical castration. The utility of a CO₂ surgical laser was evaluated on reducing behavioral and physiological indicators of pain and on the improvement of wound healing in piglets after tail docking. Tail docking with a CO₂ surgical laser caused less inflammation and tissue damage immediately after the procedure was performed compared to side pliers. Tail docking with a CO₂ surgical laser caused piglets to grimace less than piglets tail docked using side pliers. Additionally, there were no differences in pain behavior between laser and conventionally tail docked piglets. Results suggest that a CO₂ surgical laser may have the potential to refine the tail docking procedure as opposed to side pliers. The analgesic effects of transmammary delivered firocoxib to piglets was evaluated on relieving pain after tail docking and castration. Tail docking and castration caused piglets to elicit vocalizations of higher energy and peak amplitude, place more force and pressure on their front limbs than their hind limbs, and have a higher cortisol response. Pain behavior was observed more in male piglets than in female piglets after processing. However, immediately after processing, pain behavior was reduced after the administration of 3.0 and 5.0 mg/kg transmammary delivered firocoxib. The same dose of 3.0 mg/kg firocoxib reduced piglet cortisol concentrations. Results suggest that tail docking and castration cause a heightened stress and pain response in piglets as evidenced by vocalizations, pressure mat gait analysis, and cortisol. However, transmammary delivered firocoxib at a dose of 3.0 mg/kg may be effective at attenuating piglet stress and pain responses. The analgesic effects of a multimodal approach of firocoxib (oral and transmammary) and bupivacaine liposome suspension were evaluated in reducing pain associated with tail docking and surgical castration using a CO₂ surgical laser. Bleeding was reduced by using the CO₂ surgical laser for piglet tail docking only immediately after the procedure was performed. However, this tool caused more inflammation at the tail docking site than side pliers. Benefits of using a CO₂ surgical laser for surgical castration in piglets were not observed. The multimodal approach of oral firocoxib and bupivacaine liposome suspension resulted in lower cortisol concentrations and reduced changes in gait compared to transmammary delivered firocoxib and bupivacaine liposome suspension or only the bupivacaine liposome suspension block. Results suggest that oral firocoxib in combination with bupivacaine liposome suspension may provide an effective analgesic strategy at relieving pain in piglets after tail docking and castration as evidenced by cortisol and pressure mat gait outcomes. Further research is needed to assess whether a CO₂ surgical laser can refine piglet processing procedures. Lastly, the analgesic effects of a multimodal approach of firocoxib and buprenorphine were evaluated in reducing pain associated with surgical castration in male piglets. Castration caused piglets to take longer strides and produce higher concentrations of prostaglandin E₂ metabolites. However, the multimodal approach of 1.0 mg/kg IM firocoxib and buprenorphine attenuated stress and pain responses post-castration by reducing prostaglandin E₂ metabolites concentrations and alterations in weight distribution onto the front limbs. Results suggest 1.0 mg/kg firocoxib and buprenorphine may also be an effective analgesic strategy at reducing piglet pain responses after castration. In conclusion, the results presented in this dissertation indicate that tail docking and castration induce responses associated with stress and pain in piglets such as high, intense vocalizations, pain-specific-behavior, facial grimacing, inflammation, increased concentrations of cortisol and prostaglandin E₂ metabolite, and weight redistribution across the limbs. The tail docking procedure may be refined using a CO₂ surgical laser. However, evidence suggests otherwise for surgical castration. Studies also demonstrated the successful transfer of firocoxib to piglets via the sow's milk after oral administration of firocoxib to the sow. A multimodal approach of firocoxib and bupivacaine liposome suspension or firocoxib and buprenorphine may be effective options of providing analgesia to piglets in reducing pain after tail docking and castration.
Keywords: Animal welfare; Piglet; Pain; Surgical castration; Tail docking; Firocoxib